2015
DOI: 10.1088/0004-637x/806/2/220
|View full text |Cite
|
Sign up to set email alerts
|

Henize 2–10: The Ongoing Formation of a Nuclear Star Cluster Around a Massive Black Hole

Abstract: The central region of the galaxy Henize 2-10 hosts a black hole (BH) candidate with a mass Log (M BH /M ⊙ ) = 6.3 ± 1.1. While this putative black hole does not appear to coincide with any central stellar overdensity, it is surrounded by 11 young massive clusters with masses above 10 5 M ⊙ . The availability of high quality data on the structure of the galaxy and the age and mass of the clusters provides excellent initial conditions for studying the dynamical evolution of Henize 2-10's nucleus.Here we present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 68 publications
3
83
1
Order By: Relevance
“…Observationally, a NSC in a galactic nucleus is identified as an evident edge in the host galaxy surface brightness profile Turner et al 2012;Georgiev & Böker 2014;Arca-Sedda et al 2015). However, we did not found any evident edge neither in our model surface density profile, nor in the projected radial velocity profile, which is shown in Fig.…”
Section: Dynamical Friction and Tidal Disruptioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Observationally, a NSC in a galactic nucleus is identified as an evident edge in the host galaxy surface brightness profile Turner et al 2012;Georgiev & Böker 2014;Arca-Sedda et al 2015). However, we did not found any evident edge neither in our model surface density profile, nor in the projected radial velocity profile, which is shown in Fig.…”
Section: Dynamical Friction and Tidal Disruptioncontrasting
confidence: 52%
“…Moreover, the inspiralling and merger of GCs in a galaxy has found a significant support by very recent finding of RR Lyrae stars in the centre of our Galaxy (Minniti et al 2016) Using observational data of the dwarf starburst galaxy Henize 2-10, which hosts an SMBH surrounded by 11 massive clusters (Reines & Deller 2012;Nguyen et al 2014), Arca-Sedda et al (2015) have shown that the formation of a NSC is regulated by the gravitational galactic field and the SMBH, and it can occur on relatively short time-scales, < 1 Gyr. Since the Henize 2-10 clusters are young, with ages ∼ 5 Myr (Chandar et al 2003), these results suggest that NSCs can form on time scales compatible with the SMBH growth.…”
Section: Introductionmentioning
confidence: 62%
“…being τ 0 a normalization factor, g(e GC , γ) a weak function of the cluster eccentricity and the galaxy slope, α = −0.67 and β = 1.76 (see also Arca-Sedda et al 2015).…”
Section: Appendixmentioning
confidence: 99%
“…This mechanism, called dynamical friction (df), arises directly from two-body encounters and plays a significant role in shaping the evolution of astrophysical systems on very different scales (Bekenstein 1973;Tremaine 1976;Capuzzo-Dolcetta 1993;Milosavljević & Merritt 2001;Gualandris & Merritt 2008;Antonini 2013;Arca-Sedda & Capuzzo-Dolcetta 2014b;Arca-Sedda et al 2015).…”
Section: Dynamical Frictionmentioning
confidence: 99%